Host microbiota and infection outcomes in thermally extreme environments - Li, J (2023)

(untitled)
Hosts, their collection of commensal and pathogenic microbes, and the environment are all interlinked in a disease pyramid. Their interactions contribute to host fitness, particularly relevant in the context of a changing world. Climate change is leading to higher average temperatures as well as shifting the global distribution of infectious diseases, posing great risk to wildlife, ecosystem biodiversity, and human health. Host microbiomes are increasingly regarded as conferring extended phenotypes, potentially buffering host organisms against abiotic and biotic stressors. In this thesis, I combine meta-analytical and experimental approaches to explore the impact of warming temperatures and infection on ecological dynamics (i.e., microbiomes, infection disease outcomes) and evolutionary dynamics (i.e., host gene-based resistance). Firstly, I used a meta-analytic approach to investigate whether and how experimental temperatures altered host microbiome structures, across a wide range of host species. I found that experimental warming and cooling drove microbiome diversity loss, with the magnitude affected more by host habitat and experimental protocols, rather than host biological traits. I then extended this work to empirically include a biotic factor – pathogen infection – to investigate changes in Caenorhabditis elegans microbiome composition. I revealed that warming and infection could destabilize microbiome communities within hosts, but their effects were not additive. Focusing more on the impact of warming to host-pathogen interactions, I subsequently used a meta-analytic approach to tackle the relationship between warming and disease outcomes across ectothermic animals. I found that experimental warming drove higher mortality of infected hosts, with larger temperature increases associated with more host deaths. The magnitude of these effects varied by pathogen taxonomy and their evolutionary history within the host. Lastly, I zoomed out to empirically capture the possible host evolutionary paths for resistance to pathogens due to warming. I competed two C. elegans genotypes (susceptible wild-type vs. resistant mutant) across 10 host generations, varying in pathogen presence and the timing of warming during their development. I detected a loss of genetic-based resistance under periodic warming despite infection. I revealed that such host evolutionary trajectories could be driven by the combination of fitness constraints on genetic-based resistance, temperature-mediated host protection, infection severity, as well as the dilution of pathogen cells by resistant hosts. Work in this thesis is a timely contribution to our understanding of the diversity of consequences of warming to host-microbe interactions across the mutualist-parasite continuum. Biologists seeking to refine predictions of biodiversity amidst climate change should strongly consider the relationships of animals with their resident and attacking microbes.